A Case of Pharmaceutical Messianism Amidst the COVID-19 Pandemic: An Infodemiological Study of Ivermectin in the Philippines. (February 2023) - Alibudbud, Rowalt
Pharmaceutical messianism is a manifestation of medical populism. It arises during extraordinary crises, is built on the familiar, endorsed by heterodox authorities, and involves a highly accessible panacea. Amid the politics and public desperation in the Philippines during the COVID-19 pandemic, pharmaceutical messianism can be observed in the form of Ivermectin, a panacea offered to prevent and treat COVID-19. Thus, it may be worthwhile to determine the changes and patterns of public interest toward Ivermectin. This infodemiological study utilized and described Search Volume Index and related queries for Ivermectin from Google Trends vis-à-vis reported societal events in the Philippines to determine changes in public interest in Ivermectin use. It revealed that a tremendous increase in public interest in Ivermectin has emerged during surges of COVID-19 cases, endorsement by politicians and heterodox health authorities, and public distribution of Ivermectin. It also showed that public interest increased as the number of component characteristics of pharmaceutical messianism increased. Search-related queries and topics also showed that the public might be using the internet to inform themselves regarding the use of Ivermectin for humans, including its use for COVID-19. These findings suggest that people may study the endorsed panacea and weigh it against conventional and orthodox treatment during rising COVID-19 cases. Thus, easily understandable, highly searchable, reliable, and trustworthy online information is ever-crucial in this age of information and disinformation.